TEACHING METHODS OF WRITING SKILLS TO CHILDREN - Allaberdiyeva Muniba; Rasulova Sohiba Ulug'bekovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Writing is a speech activity that provides expression of thought in graphic form effective type. Written and spoken foreign language in the methodology of teaching a foreign language is both a means and a goal of education. Writing is a technique of written speech is a component. Written speech is a productive type of speech activity along with speech, it is expressed in defining some content through graphic symbols. Having good writing skills may assist you in conveying information in a more comprehensive, informative, clear and direct manner. The ability to write effectively and precisely is an important skill, especially in a professional environment. In this article, we discuss how to teach writing skills, the approaches to teaching writing and the stages of the writing process and we provide some tips to help you improve your teaching skills.